Risk factors associated with bloodstream infections among critically ill patients with COVID-19. Issue 5 (November 2021) - McMillan, Tim; Jones, Conor; O'Connor, Cavan J; Nolan, Daniel; Chan, Xin Hui S; Ellis, Jayne; Thakker, Clare; Kranzer, Katharina; Stone, Neil RH; Singer, Mervyn; Wilson, A Peter R; Arulkumaran, Nishkantha
Highlights: Approximately one in five critically ill patients with COVID-19 develop a bloodstream infection (BSI). The median time from hospital admission to developing a BSI was 18 days. Tocilizumab and dexamethasone are not associated with increased risk of BSI.